Pro-Inflammatory Cytokine-Mediated Anemia: Regarding Molecular Mechanisms of Erythropoiesis - F. Morceau; M. Dicato; M. Diederich (Mediators of Inflammation)
Anemia of cancer and chronic inflammatory diseases is a frequent complication affecting quality of life. For cancer patients it represents a particularly bad prognostic. Low level of erythropoietin is considered as one of the causes of anemia in these pathologies. The deficiency in erythropoietin production results from pro-inflammatory cytokines effect. However, few data is available concerning molecular mechanisms involved in cytokine-mediated anemia. Some recent publications have demonstrated the direct effect of pro-inflammatory cytokines on cell differentiation towards erythroid pathway, without erythropoietin defect. This suggested that pro-inflammatory cytokine-mediated signaling pathways affect erythropoietin activity. They could interfere with erythropoietin-mediated signaling pathways, inducing early apoptosis and perturbing the expression and regulation of specific transcription factors involved in the control of erythroid differentiation. In this review we summarize the effect of tumor necrosis factor (TNF)α, TNF-related apoptosis-inducing ligand (TRAIL), and interferon (IFN)-γ on erythropoiesis with a particular interest for molecular feature.